COLONIALISM AND INDUSTRIAL DEVELOPMENT IN BENIN PROVINCE, NIGERIA - Frank Ikponmwosa (Romanian Journal of Historical Studies, 2020)
This paper examines colonialism and the development of industry in Benin Province of Nigeria. It identifies and discusses various aspects of the Benin economy that requires the use of simple machines or mechanical instrument in the production processes. In this respect, the paper begins by attempting to examine the purpose of colonial rule and how it largely influenced or impaired industrial development in Benin. The study is descriptive in nature and covers three main areas of the Benin province including Benin Division, Ishan Division and Kukuruku Division which were administrative units created by the British following the occupation of Nigeria. In contemporary time, these divisions formed the core of Edo state in southern Nigeria with its administrative capital in Benin City. The study uses data from primary and secondary sources. The data were analysed in order to arrive at possible conclusion on the nature of industries inherited at independence.